A devil and her love song. Volume 13 - Tōmori, Miyoshi (Viz Media, 2014)
Maria's boyfriend Shin is living abroad, and Maria is uncertain about their future together. With the end of high school fast approaching, she faces some tough decisions. Her friends encourage her to keep singing, but will Shin respond to this devil's love song?